2001
DOI: 10.1002/1521-3927(20010301)22:5<315::aid-marc315>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

60Co γ-Irradiation-Initiated “Living” Free-Radical Polymerization in the Presence of Dibenzyl Trithiocarbonate

Abstract: The free‐radical polymerization of vinyl monomers in the presence of dibenzyl trithiocarbonate (DBTTC) and under 60Co γ‐irradiation is of living character. Under 60Co irradiation, the bonds between benzyl group and sulfur were cleaved, benzyl radicals initiate the polymerization. The propagating radical together with trithiocarbonate radicals form a dormant polymer chain. The fast equilibrium between propagation radical and dormant polymer chain controls the polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 8 publications
3
97
0
Order By: Relevance
“…AIBN, ACP, K 2 S 2 O 8 ) are used. Styrene polymerization may be initiated thermally between 100 and 120 • C. Polymerizations initiated with UV irradiation, [142,143] a γ-source, [144][145][146][147][148][149] or a plasma field [150] have been reported. In these polymerizations, radicals may be generated directly from the RAFT agent and these may be responsible for initiation.…”
Section: Initiation and Termination In Raft Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…AIBN, ACP, K 2 S 2 O 8 ) are used. Styrene polymerization may be initiated thermally between 100 and 120 • C. Polymerizations initiated with UV irradiation, [142,143] a γ-source, [144][145][146][147][148][149] or a plasma field [150] have been reported. In these polymerizations, radicals may be generated directly from the RAFT agent and these may be responsible for initiation.…”
Section: Initiation and Termination In Raft Polymerizationmentioning
confidence: 99%
“…In these polymerizations, radicals may be generated directly from the RAFT agent and these may be responsible for initiation. It was suggested by Pan and coworkers that the mechanism for molecular weight control in UV [143] and γ-initiated [147] processes might involve reversible coupling and be similar to that proposed by Otsu et al [151] to describe the chemistry of dithiocarbamate photoiniferters. However, Quinn et al [142,145] have demonstrated that the living behaviour observed in these polymerizations can be attributed to the standard RAFT mechanism (Scheme 6).…”
Section: Initiation and Termination In Raft Polymerizationmentioning
confidence: 99%
“…[1 -3] Conflicting mechanisms have been proposed to explain the observed experimental behaviour. Bai et al attribute the living behaviour to a reversible termination mechanism, [1,2] while Quinn et al [3] propose a reversible addition-fragmentation chain transfer (RAFT) mechanism. The current Communication seeks to differentiate between the two mechanisms and therefore isolate the true origin of living behaviour under gamma radiation at low dose rates.…”
Section: Introductionmentioning
confidence: 99%
“…evolution of molecular weight with conversion, low polydispersity index and pseudo first order kinetics. Scheme 2 shows the alternative explanation offered by Bai et al [1] for living behaviour under a constant source of gamma radiation. Under this scheme, gamma radiation would need to induce selective and sequential homolytic cleavage of the carbon sulfur bond in the dithioester, yielding a stable thiocarbonylthiyl radical.…”
Section: Introductionmentioning
confidence: 99%
“…6 In the case of 60 Co c-irradiation condition, DBTTC catalyze living radical polymerization of methyl methacrylate as well as styrene and methyl acrylate. 7 Controlled alternating copolymer of styrene and maleic anhydride is also obtained by the DBTTC. 8 RAFT polymerizations using other benzyl trithiocarbonates can be applicable to welldefined block copolymer, star polymer, and dendric polymer.…”
Section: Introductionmentioning
confidence: 99%